Does openness/intellect predict sensitivity to the reward value of information? - Smillie, Luke D.; Bennett, Daniel; Tan, Nicholas P.; Sutcliffe, Kiran; Fayn, Kirill; Bode, Stefan; Wacker, Jan (Cognitive, Affective & Behavioral Neuroscience, 2021)
A recent theory proposes that the personality trait openness/intellect is underpinned by differential sensitivity to the reward value of information. This theory draws on evidence that midbrain dopamine neurons respond to unpredicted information gain, mirroring their responses to unpredicted primary rewards. Using a choice task modelled on this seminal work (Experiment 1, N = 139, 69% female), we examined the relation between openness/intellect and willingness to pay for non-instrumental information (i.e., information with no secondary utility). We also assessed whether any such relation was moderated by the dopamine D2 receptor antagonist sulpiride (Experiment 2, N = 164, 100% male). Unexpectedly, most measures of openness/intellect were unrelated to costly information preference in both experiments, and some predicted a decreased willingness to incur a cost for information. In Experiment 2, this cost-dependent association between openness/intellect and information valuation appeared in the placebo condition but not under sulpiride. In addition, participants were more willing to pay for moderately costly information under sulpiride compared to placebo, consistent with a dopaminergic basis to information valuation. Potential refinements to the information valuation theory of openness/intellect are discussed in the light of these and other emerging findings.